Expressive Speech Acts Analysis of Percy Jackson’s Movie (2010) - Mareta, Dinar Rosiana; Afriana, Afriana (Anaphora : Journal of Language, Literary, and Cultural Studies, 2024)
Illocutionary activities include expressive acts among their types. This study aimed to find and identify types of expressive speech acts. This study used theories from Searle and Vanderveken (1985) by analyzing the film Percy Jackson (2010). Researchers used qualitative methods to collect the data. Researchers used observation methods and note-taking techniques. For analysis, this study used qualitative data analysis by Flick (2014). In the results of this study, researchers chose 15 data because the words or sentences often appear in the characters' conversations. These 15 data are also a means of taking action in conversations related to the delivery and context of a topic carried out by the characters. All types of expressive speech acts are found in this film. Apologize type 7 times, thank type 20 times, congratulate type 5 times, boast type 12 times, compliment type 33 times, welcome type 5 times, greet type 20 times, complain type 30 times, protest type 34 times, condole type 1 time, lament type 3 times, and deplore type 1 time. Based on the utterances of the characters, protest, and compliment are the most prevalent types in this film because the characters in this film express a lot of their protest about something they do not like and express compliments to each other to encourage them if they are doing well. This speech act is used to express feelings and is a way of giving understanding to the viewers of this film.